The mandate to disclose energy performance lowers house prices - Andreas Gerster (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
New legislation increases transparency in the real estate market and reduces the asking price of houses with high energy consumption. - As of May 1, 2014, sellers on the German real estate market are obliged to disclose a house's energy consumption per square meter in their advertisements. The effect of this law has been to substantially increase the transparency of the real estate market. At the same time, the introduction of mandatory disclosure had impacts on asking prices: Houses with poor thermal quality became cheaper, with no price change seen for houses with high thermal quality. This is likely due to the fact that sellers of houses with high energy consumption typically did not include this information in their advertisement before the new regulation.
Keywords: 330